2006
DOI: 10.1300/j021v26n04_05
|View full text |Cite
|
Sign up to set email alerts
|

New Learning Programs in Cognitive Vitality, Alzheimer's Disease, and Related Dementias

Abstract: As the population continues to age there remains an unmet need in preventing, identifying, treating, and managing mental/behavioral health problems among older adults. The purpose of this paper is to describe educational and training programs offered through three Geriatric Education Centers: (1) the Meharry Consortium Geriatric Education Center, which offers a certificate program on Cognitive Vitality dispelling myths that dementias are part of the normal aging process, (2) the Harvard Upper New England Geria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 12 publications
(3 reference statements)
0
2
0
Order By: Relevance
“…Research that dealt with aspects of education for late-life dementia and Alzheimer's patients was published by Kovacich et al [41]. McDowell et al then deal with sessions and educational opportunities for patients affected by dementia [42].…”
Section: Literature Reviews Sectionmentioning
confidence: 99%
“…Research that dealt with aspects of education for late-life dementia and Alzheimer's patients was published by Kovacich et al [41]. McDowell et al then deal with sessions and educational opportunities for patients affected by dementia [42].…”
Section: Literature Reviews Sectionmentioning
confidence: 99%
“…Copy@ Boniface Harerimana Besides the inconsistency in defining attributes, cognitive vitality as a concept varies across disciplines. For instance, in gerontology, cognitive vitality is used to denote the maintenance of cognitive functioning that enables the elderly to adapt to brain changes with aging and to sustain their well-being within their living environment [14][15][16]. However, in neurobiology, it is used to refer to either cognitive health or an absence of cognitive decline, i.e.…”
Section: American Journal Of Biomedical Science and Researchmentioning
confidence: 99%
“…A review of gerontology evidence by [16] demonstrated that the importance of lifestyle choices in protecting cognitive vitality [16] found diet rich in E vitamins and mental exercise, such as that keeps the mind active exert a protective effect on cognitive vitality.…”
Section: Gow Et Al [45]mentioning
confidence: 99%